Nanoporous carbon@CoFe2O4 nanocomposite as a green absorbent for the adsorptive removal of Hg(ii) from aqueous solutions - Abubakar, Lawal; Yusof, Nor Azah; Abdullah, Abdul Halim; Wahid, Mohd Hanif; Abd Rahman, Siti Fatimah; Mohammad, Faruq; Al-Lohedan, Hamad A.; Soleiman, Ahmed A. (Walter de Gruyter GmbH, 2023)
To address the harmful pollutants found in heavy metals and agricultural waste, researchers have worked on creating various materials that can capture these pollutants. They have experimented with altering the shape, size, structure, surface properties, and bioactive components of these materials. This study aims to improve the effectiveness of materials used for adsorption, focusing on the combination of cobalt spinal ferrite (CoFe2O4) and nanoporous carbon (NC) obtained from discarded palm kernel shells with the aim of Hg(ii) removal. The composite formed by the hydrothermal method was characterized thoroughly with morphological, structural, functional, pore sizes, thermal analysis, and magnetization analysis. Adsorption experiments were conducted under optimal conditions with a mass of 0.3 g, a concentration of 30 mg·L−1 of Hg(ii), and a pH of 3. The aim was to adsorb Hg(ii) ions from aqueous solutions. The analysis of kinetic studies using the Freundlich model revealed that it provided the most accurate fit for the adsorption isotherm. This model indicated a maximum Hg(ii) adsorption efficiency of 232.56 mg·g−1. Additionally, the thermodynamic measurements indicate that the adsorption is a spontaneous, favorable, and endothermic process. Likewise, we assessed how well the NC@CoFe2O4 nanocomposite could absorb Hg(ii) ions in actual condensate samples from the oil and gas industry. The results demonstrated a 93% recovery rate for Hg(ii) ions in wastewater. According to the findings, the NC@CoFe2O4 nanocomposite synthesized appears to be a strong contender for wastewater treatment and, at the same time, the prepared nanocomposite’s effectiveness, affordability, and non-toxic nature support the potential applications.